2012
DOI: 10.4015/s1016237212500408
|View full text |Cite
|
Sign up to set email alerts
|

Relative Motion of Tendon Limbs in a Loop Tendon Graft

Abstract: The biomechanical data derived from the standard tensile testing machines may not be able to show the relative motion of the graft limbs. This paper uses a digital stereo image recording system, synchronized with the standard test machine, to determine the relative motion of a looped tendon graft. Bovine°exor tendon was used to create the looped graft and then the graft was passed through a tunnel in a foam block and¯xed with an interference screw. The structure was then mounted in a testing machine. The tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…By maintaining the four-tailed end of the tendon bundle, a 10 mm diameter interference screw was screwed into the entrance (anterior aspect) of the tunnel between the tendon strands and moved forward until its tip reached the proximal bone-tunnel opening (Fig.1 c). A general biomechanical test, i.e., tensile test as described previously [14][15][16], was performed on the bone and tendon to observe the placement of the graft and screw in the bone tunnel after the mechanical loading. The loop portion of the tendon hanged with the crosshead of the testing machine, and the bone was secured using custom-made grips in the testing machine (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By maintaining the four-tailed end of the tendon bundle, a 10 mm diameter interference screw was screwed into the entrance (anterior aspect) of the tunnel between the tendon strands and moved forward until its tip reached the proximal bone-tunnel opening (Fig.1 c). A general biomechanical test, i.e., tensile test as described previously [14][15][16], was performed on the bone and tendon to observe the placement of the graft and screw in the bone tunnel after the mechanical loading. The loop portion of the tendon hanged with the crosshead of the testing machine, and the bone was secured using custom-made grips in the testing machine (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After that, if the structure was not failed in previous stages, a load-to-failure test was carried out at a rate of 20 mm/min [14,16]. Failure was characterized either by tendon rupture or when significant slip-up occurs at fixation [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…ACL reconstruction has been widely investigated by many researchers from different aspects of clinical and bioengineering viewpoints [3, 4]. The majority of previous researchers concluded that the tibial fixation is the weakest link in ACL reconstruction [1, 2].…”
Section: Strength Of Fixationmentioning
confidence: 99%
“…According to previous researches pertaining to skin, animal skins have been the main samples and focus of study, prepared and tested using the in-vitro procedure. Murine, bovine and rabbit skins were studied to investigate the biomechanical parameters [3][4][5]. On the other hand, several articles have studied and discussed about the investigation of human skin.…”
Section: Introductionmentioning
confidence: 99%